Estudo sobre características genéticas de Mycobacterium tuberculosis isolados de pacientes com e sem lesões cavitárias - Vinhas, Solange Alves (2013)
Background: Based on the hypothesis that genetic variability of Mycobacterium tuberculosis (MTB) could influence virulence and immunopathology we analyzed genetic profiles of different MTB strains in order to detect relatedness between genetic diversity and presence of cavity (disease severity). Methods: We conducted a retrospective molecular study in Vitória ES, based on TB strains (2003 to 2006, n = 214) from patients with pulmonary cavitary and non-cavitary TB using IS6110-RFLP, Spoligotyping and MIRU-VNTR methodologies. RESULTS: Initially, we compared the association of the demographic and clinical characteristics of patients with the presence of cavities. After logistic regression the variables that most contributed to explain the model of the disease were smear positive (ORajust = 5.96; IC= 2.58-13.73) and sputum production (ORajust = 4.55; IC= 1.28-16.12), there was no statistically significant association with the remaining variables. The LAM family was the most frequent within the samples of the two groups analyzed, representing 65 (62%) of the isolates in the cavitary group and 40 isolates (38%) of the non-cavitary. After comparing the proportions of LAM and other spoligotyping families there was no statistically significant difference between the groups (p=0.17). In relation to deletions RDRio (p=0.65) and RD174 (p=0.65) there were no statistically significant difference between the groups. Amongst the 205 isolates analyzed, 25 (12%) belonging to the non-cavitary group and 43 (21%) belonging to the cavitary group, were grouped in clusters. The statistical analysis of the association of the occurence of clusters with the presence of cavity showed no statistically significant difference between the quantity of clusters and the groups that were analyzed, (p= 0.4). Conclusion: The genotipic profile for the isolates from patients with cavitary and non-cavitary disease was determined. Our data showed that LAM9 was the most frequent among the strains between cavitary and noncavitary groups, corroborating findings that this family is the most frequent in Brasil. There were no statistical differences that could show association among the variables analyzed related to presence of cavity or disease severity